Organic Food: The Factors Influencing Consumers' Purchasing Intention - Rakotoarisoa Maminiaina Heritiana Sedera; Ronaldo Yolanda Putra; Eka Kurnia Saputra; Muhammad Ahmad Ali (Jurnal Manajemen Teori dan Terapan, 2023)
Objective: This investigation assessed the factors determining consumers' purchasing intention for natural food. This study employs four variables to explain the phenomenon: purchasing intention toward organic food, altruistic value, egoistic value, and attitude toward organic products.